Once upon a broken heart - Garber, Stephanie (Once upon a broken heart, 2021)
Desperate to stop her beloved from marrying another, sixteen-year-old Evangeline Fox strikes a deal with the mythic Prince of Hearts leading her down a dangerous path that may ultimately end in her destruction.